Ambulation in Dogs With Absent Pain Perception After Acute Thoracolumbar Spinal Cord Injury - Lewis, Melissa J.; Jeffery, Nick D.; Olby, Natasha J.; , The Canine Spinal Cord Injury Consortium (CANSORT-SCI); Moore, Sarah A.; Olby, Natasha J.; Gjessing, Kady M.; Davidson, Rhanna M.; Levine, Jonathan M.; McWhorter, Helen; Lewis, Melissa J.; Jeffery, Nick D.; et al. (Frontiers in Veterinary Science, 2020)
Acute thoracolumbar spinal cord injury (SCI) is common in dogs frequently secondary to intervertebral disc herniation. Following severe injury, some dogs never regain sensory function to the pelvic limbs or tail and are designated chronically ‘deep pain negative.’ Despite this, a subset of these dogs develop spontaneous motor recovery over time including some that recover sufficient function in their pelvic limbs to walk independently without assistance or weight support. This type of ambulation is commonly known as ‘spinal walking’ and can take up to a year or more to develop. This review provides a comparative overview of locomotion and explores the physiology of locomotor recovery after severe SCI in dogs. We discuss the mechanisms by which post-injury plasticity and coordination between circuitry contained within the spinal cord, peripheral sensory feedback, and residual or recovered supraspinal connections might combine to underpin spinal walking. The clinical characteristics of spinal walking are outlined including what is known about the role of patient or injury features such as lesion location, timeframe post-injury, body size and spasticity. The relationship between the emergence of spinal walking and electrodiagnostic and magnetic resonance imaging findings are also discussed. Finally, we review possible ways to predict or facilitate recovery of walking in chronically deep pain negative dogs. Improved understanding of the mechanisms of gait generation and plasticity of the surviving tissue after injury might pave the way for further treatment options and enhanced outcomes in severely injured dogs.